1998
DOI: 10.1183/09031936.98.11020384
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced epithelial injury: the protective role of intracellular nonprotein thiols (NPSH)

Abstract: Injury to the alveolar region is a hallmark of the adult respiratory distress syndrome (ARDS) whereas injury to the epithelium of the conducting airways is a characteristic of asthma. Reactive oxygen species have been implicated as mediators of lung injury in both of these conditions. We have investigated the relationship between intracellular nonprotein thiols (NPSH), and the release of the cytosolic enzyme lactate dehydrogenase (LDH), as an index of cell injury, following treatment of the human alveolar type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 35 publications
4
35
0
7
Order By: Relevance
“…AT-2 cells were stimulated with hydrogen peroxide (H 2 O 2 , 0.5 mM, Xilong Chemical Factory, China). A dose of H 2 O 2 was chosen that was consistent with previous reports [28,29] and with our pilot study, in which we found that a lower dose (0.25 mM) of H 2 O 2 did not induce obvious AT-2 cells injury. At 0, 1, 2, 4, 8, 16, 24 h after treatment, cells were harvested and mRNA and protein was extracted to determine FoxA1 expression.…”
Section: Cell Culture and Induction Of Acute Cell Injurysupporting
confidence: 55%
“…AT-2 cells were stimulated with hydrogen peroxide (H 2 O 2 , 0.5 mM, Xilong Chemical Factory, China). A dose of H 2 O 2 was chosen that was consistent with previous reports [28,29] and with our pilot study, in which we found that a lower dose (0.25 mM) of H 2 O 2 did not induce obvious AT-2 cells injury. At 0, 1, 2, 4, 8, 16, 24 h after treatment, cells were harvested and mRNA and protein was extracted to determine FoxA1 expression.…”
Section: Cell Culture and Induction Of Acute Cell Injurysupporting
confidence: 55%
“…NAc is capable of scavenging hydrogen peroxide and hydroxyl radicals. Pretreatment of human alveolar and bronchial epithelial cells with NAc attenuates the injurious effects of hydrogen peroxide (45). In addition, DPI (a flavoprotein inhibitor) and APO (an inhibitor of translocation of the oxidase subunits) have been shown to prevent p47 phox translocation to the membrane (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is able to scavenge H 2 O 2 , hydroxyl radicals, and hypochlorous acid (11). Pretreatment of human alveolar and bronchial epithelial cells with NAC protects both cell types against injurious effects of H 2 O 2 (174). It has also been shown that NAC protects against hypochlorous acid-induced contraction of guinea pig tracheal smooth muscles (19) and inhibits LPS-induced leukocyte accumulation in rat lungs.…”
Section: Thiolsmentioning
confidence: 99%